2013
DOI: 10.1371/journal.pntd.0002002
|View full text |Cite
|
Sign up to set email alerts
|

The Laboratory Diagnosis and Follow Up of Strongyloidiasis: A Systematic Review

Abstract: BackgroundStrongyloidiasis is frequently under diagnosed since many infections remain asymptomatic and conventional diagnostic tests based on parasitological examination are not sufficiently sensitive. Serology is useful but is still only available in reference laboratories. The need for improved diagnostic tests in terms of sensitivity and specificity is clear, particularly in immunocompromised patients or candidates to immunosuppressive treatments. This review aims to evaluate both conventional and novel tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
379
2
22

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 333 publications
(408 citation statements)
references
References 117 publications
(158 reference statements)
5
379
2
22
Order By: Relevance
“…Strongyloides stercoralis is a soil transmitted intestinal nematode, primarily known as a parasite in humans and dogs (Shoop et al 2002), but also found in non-human primates and cats (Grove 1996, Júnior et al 2006 causing the disease strongyloidosis (Goncalves et al 2007, Requena-Méndez et al 2013. The life cycle is complex and involves both a freeliving developmental cycle and a parasitic life cycle (Shoop et al 2002, Bowman 2009, and autoinfection can occur within the host (Olsen et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Strongyloides stercoralis is a soil transmitted intestinal nematode, primarily known as a parasite in humans and dogs (Shoop et al 2002), but also found in non-human primates and cats (Grove 1996, Júnior et al 2006 causing the disease strongyloidosis (Goncalves et al 2007, Requena-Méndez et al 2013. The life cycle is complex and involves both a freeliving developmental cycle and a parasitic life cycle (Shoop et al 2002, Bowman 2009, and autoinfection can occur within the host (Olsen et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…La detección microscópica de las larvas de S. stercoralis en las heces puede realizarse por varios métodos 5 , siendo el examen directo en heces el que se utiliza de manera rutinaria en los laboratorios clíni-cos, aunque debido a su baja sensibilidad en la detección de este nemátodo, en algunas ocasiones se requieren procedimientos que aumenten la sensibilidad de la prueba, como son el análisis de varias muestras, para aumentar la probabilidad de detección de las larvas 16,17 o las técni-cas de concentración, entre las que se encuentra la técnica de formol-éter, formalina etil acetato y sedimentación espontánea o Hoffman [18][19][20] . Otras técnicas utilizadas para el diagnóstico de S. stercoralis son la técnica de Bearman y el en placa de ágar 21 .…”
Section: Introductionunclassified
“…Recently, two recombinant antigens (32 kD recombinant antigen, called NIE and S. stercoralis immmunoreactive antigen, SsIR) have been employed for serological testing in both ELISA and luciferase immunoprecipitation system assay (LIPS) platforms 15 . The reported sensitivity and specificity of various serological platforms ranges from 56-100% and 29-100%, dependent upon the method, antigens, cut-offs, study populations, and reference methods employed 16 . Strongyloides serology using a crude larval extract antigen was shown in one study to be less sensitive for the diagnosis of returned travellers (73%) compared to patients who have lived for an extended period in an endemic area (98%) 17 .…”
Section: Serological Diagnosismentioning
confidence: 99%
“…NIE LIPS did not cross-react with antigens from other parasites in the study by Bisoffi et al, whereas IFAT and the two commercial ELISAs did yield false positives, particularly from Mansonella perstans infection 14 . Such cross-reaction may be decreased by pre-incubation of serum in an extract of Onchocerca gutterosa 16 .…”
Section: Serological Diagnosismentioning
confidence: 99%